Peripheral Computations: The Basis for Data Processing in Internet of Things - O. L. YERSHOVA; Т. V. TOMASHEVSKA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
Internet of Things (ІоТ) is a global mainstream trend of today, which determines the importance of studies dealing with problems related with data processing by use of ІоТ.  A definition to the notion “Internet of Things” is given, with stressing that peripheral computing is a new trend for connected devices of IoT. The main applications of IoT are described. Peripheral computing is compared with cloud and fog computing. The need for peripheral computing in the conditions of “smart” life is demonstrated. Various forms of the launched peripheral computing infrastructure are discussed. The need for peripheral computing in the software based on IoT technology is justified. It is shown that IoT pushes up the demand for peripheral computing. Real examples of successful applications of peripheral computing and IoT across industries are shown.   It is stressed that the strongest impediment for the massive dissemination of IoT is that its infrastructure involves infinite numbers of options for connection, which may be quite often fully incompatible with each other. It is argued that peripheral computing is needed to remove drawbacks in software design and services on the basis of cloud technologies with consideration to performance and normative requirements. The forms of peripheral computing infrastructure are shown and described: special local devices, localized or regional data processing centers. The purpose of IoT technology is mentioned, which is the collection of large scopes of data from great many censors and smart devices, to be employed for business performance enhancement. The main reasons for the necessity of peripheral computing in the software based on IoT technology are outlined: the need to increase the throughput, the possibility to minimize the delay in data transmission and processing, and normative requirements. The main advantages of digital technology introduction are highlighted: better comfort of clients, higher exploitation efficiency, creation of new income flows.